Splenosis in gastric fundus mimicking gastrointestinal stromal tumor: a report of two cases and review of the literature - Li, Bin (Int J Clin Exp Pathol, 2015)
Splenosis refers to heterotopic autotransplantation and implantation of splenic tissue following splenic trauma or surgery. Splenosis in gastric fundus is rare and difficult to diagnose, since splenosis has similar manifestation with gastrointestinal stromal tumor (GIST) under routine endoscopy examination. In this report, we present two quite rare case of splenosis. Both of their pre-operative diagnose under endoscopic ultrasonography was considered as GIST. Finally, one in the abdominal cavity, adhering closely to the gastric fundus, measuring 20 mm × 15 mm, was resected by surgical operation, and one in the gastric fundus, measuring 20 mm × 20 mm, was resected by endoscopic surgery. The precise diagnosis of splenosis was distinct by post-operative histopathologic examination. In addition, we also made a mini review of previously published articles, in order to provide indication to solve future doubts in diagnosing and treating splenosis.